Comparison of mercury sphygmomanometry blood pressure readings with oscillometric and central blood pressure in predicting target organ damage in youth. Issue 3 (June 2015) - Urbina, Elaine M.; Khoury, Philip R.; McCoy, Connie E.; Daniels, Stephen R.; Dolan, Lawrence M.; Kimball, Thomas R.
Abstract : Objective: Hypertension (HT) is an important risk factor for target organ damage (TOD). New methods for measuring BP are replacing mercury sphygmomanometry in many clinics. We examined the utility of different BP measurement techniques in predicting subclinical TOD in adolescents and young adults. Methods: Participants in a study of the cardiovascular effects of obesity and type 2 diabetes were evaluated ( N =677, 18±3.3 years, 35% male, 60% non-White, 30% with type 2 diabetes). We measured adiposity, laboratory data, left ventricular mass, carotid intima-media thickness, and pulse wave velocity. BP was measured three times by mercury sphygmomanometry (BPm), using an oscillometric device (BPo), and by arterial tonometry to measure central aortic BP (BPc). Participants were stratified as normotensive, prehypertensive, or hypertensive. Results: The prevalence of HT in this cohort with a mean BMI of 31 was the highest on BPo measurement (16%), followed by BPm (11%) and BPc (9%; P ⩽0.001) measurements. BPm was the most consistent in differentiating left ventricular mass and pulse wave velocity among participants in the prehypertensive group as compared with the normotensive and hypertensive groups. Mercury BP measurement was also more sensitive and specific at predicting greater left ventricular mass, pulse wave velocity, and carotid thickness compared with other BP measurement techniques in logistic regression. Conclusion: We conclude that mercury sphygmomanometry should remain the gold standard for evaluation of HT and the risk for TOD in adolescents and young adults.